Nitrogênio no crescimento da planta e na qualidade de raízes da mandioquinha-salsa - Nunes, Amanda Rodrigues Alves [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Leonel, Magali [UNESP]; Garcia, Emerson Loli [UNESP]; Magolbo, Luis Augusto [UNESP]; do Carmo, Ezequiel Lopes (FapUNIFESP (SciELO), 2016)
Nitrogen (N) is the second most absorbed nutrient by Arracacha. However, there are still doubts about the influence that this nutrient can have on plant growth and the quality of the storage roots. Thus, the aim of this research was to evaluate the influence of nitrogen fertilization on plant growth and physical-chemical and nutritional quality of storage roots of Arracacha. The experiment was conducted on an Oxisol of sandy texture, in a randomized complete block design, with four replications. The treatments consisted of rates of 0, 50, 100, and 200kg ha-1 N. Growth of vegetative parts of Arracacha increased linearly with nitrogen fertilization, but the storage root mean weight and the yield of storage roots increased up to estimated rates of 121 and 148kg ha-1 N, respectively. Nitrogen fertilization increased the starch and protein content of the storage roots and reduced the content of total sugar, but without affecting the nutritional quality of the same.
Nitrogen on plant growth and storage root quality of arracacha
Keywords: Arracacia xanthorrhiza; Mineral content; Protein content; Storage root yield